Exploring the role of verbal fluency in L2 Vocabulary Learning: Evidence from university students in the United Kingdom - García-Castro, Verónica (2022)
Research in second/foreign (L2) vocabulary learning has recently started to take into account the role of learners’ individual differences in working memory, motivation, language aptitude, phonological awareness, amongst others. However, much research up to now has not explored if verbal fluency capacity influences learning L2 English in adult learners. Thus, this study examined the possible influence of verbal fluency in L1 and L2 vocabulary learning in university students (n=58) in York, United Kingdom, from March to May 2018. A quantitative methodology, via a linguistic experiment, was employed to explore whether verbal fluency capacity facilitates L1 and L2 vocabulary learning. The experiment started with a verbal fluency capacity test, followed by a vocabulary training phase, and it finished with offline recognition and recall vocabulary post-tests. Data was processed and analysed using the statistical package R and two general linear models were created and tested with the “glm” package in the R environment. Results of general linear modelling confirmed that L1 learners scored higher than L2 learners in recognition (β =-31.54, SE= 9.38, Z=-3.362, p<0.001) and recall (β = -25.50, SE= 8.69, Z=-2.933, p<0.003) vocabulary post-tests. Additionally, L1 (M=0.53; SD=0.50; vs. M=0.47; SD=0.50) and L2 learners (M=0.39; SD=0.49; vs. M=0.36, SD=0.48) with higher verbal fluency capacity scored higher in recall post-tests (β =0.83, SE=0.33, Z=2.511, p<0.012) than those with lower capacities. It is concluded that verbal fluency capacity may influence vocabulary learning and that this information should be taken into account in vocabulary teaching and learning processes.